Kondisi Geografis Sungai Indus dan Pengaruhnya terhadap Kehidupan Sosial Masyarakat di Lembah Indus - Tamara Dwi Putri; Aulia Namira Zahra; Adinda Pricillia Sari; Sani Safitri; M. Taofik Kurohman (Jurnal Ilmu Sosial dan Humaniora, 2026)
Geographical conditions play a crucial role in the development of human civilization, particularly in communities living along riverbanks. One important example is the Indus River, which was the center of the development of the Indus Valley civilization. This study aims to determine the geographical conditions of the Indus River and its influence on the social life of the people in the Indus Valley region. The method used in this study is a qualitative method with a literature study approach through a review of books, scientific journals, and relevant academic articles. The results show that the geographical conditions of the Indus River, with its long flow, extensive tributary network, and fertile alluvial soil, support the development of agriculture, trade, and social organization. These factors encourage the formation of large cities with planned urban planning systems and organized social life. Thus, the geographical conditions of the Indus River play a significant role in shaping the social and economic life patterns and the development of civilization in the Indus Valley.